'Cowering Women, Combative Men?': Femininity, Masculinity, and Ethnicity on Strike in Two Southern Ontario Towns, 1964-1966 - Ventresca, Robert (Labour/Le Travailleur, 1997)
In August 1964, the southern Ontario local 523 of the United Electrical and Radio Machine Workers led some 450 female auto-parts workers onto the picket-line. A year later, the same union local led over 1,200 male steelworkers in a strike against the Steel Company of Canada. In both cases, Italian immigrants joined with their non-Italian co-workers in a show of class solidarity. Italian men framed their decision to strike in terms of a manly duty as the family's decision maker and breadwinner; Italian women assumed the role of aggressive labour militant with relative equanimity, while the more outwardly militant Italian men expressed considerable personal uncertainty and fear even while they engaged in a public display of cross-ethnic class solidary. The paper explores how gender, class and ethnicity interact to influence the dynamics of labour militancy in the two strikes, though it also gives due consideration to the structural factors that helped to determine the outcome of both strikes.